2023
DOI: 10.2147/dmso.s391781
|View full text |Cite
|
Sign up to set email alerts
|

A Multifactorial Risk Score System for the Prediction of Diabetic Kidney Disease in Patients with Type 2 Diabetes Mellitus

Abstract: Purpose In-depth investigations of risk factors for the identification of diabetic kidney disease (DKD) in type 2 diabetes mellitus (T2DM) are rare. We aimed to investigate the risk factors for developing DKD from multiple types of clinical data and conduct a comprehensive risk assessment for individuals with diabetes. Methods We carried out a case-control study, enrolling 958 patients to identify the risk factors for developing DKD in T2DM patients from a database esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Several studies have identified hyperglycemia, serum uric acid (SUA), and platelets as risk factors for DKD in DM patients, associating them with increased risk of microalbuminuria, rapid eGFR decline, and progression to end-stage renal disease (ESRD). [36][37][38][39] Our findings in the normal lactate level group corroborated these observations, demonstrating significantly higher blood glucose, SUA, and platelet levels of DKD patients compared to those in T2DM patients without DKD, establishing them as independent risk factors for DKD. Current studies have suggested that hyperglycemia triggers oxidative stress and inflammation through activation of signaling pathways such as NF-κB, PI3K/Akt, and MAPK/ERK, ultimately contributing to DKD pathogenesis.…”
Section: Discussionsupporting
confidence: 84%
“…Several studies have identified hyperglycemia, serum uric acid (SUA), and platelets as risk factors for DKD in DM patients, associating them with increased risk of microalbuminuria, rapid eGFR decline, and progression to end-stage renal disease (ESRD). [36][37][38][39] Our findings in the normal lactate level group corroborated these observations, demonstrating significantly higher blood glucose, SUA, and platelet levels of DKD patients compared to those in T2DM patients without DKD, establishing them as independent risk factors for DKD. Current studies have suggested that hyperglycemia triggers oxidative stress and inflammation through activation of signaling pathways such as NF-κB, PI3K/Akt, and MAPK/ERK, ultimately contributing to DKD pathogenesis.…”
Section: Discussionsupporting
confidence: 84%
“…Subsequent screening of titles and abstracts reduced the pool to 759 articles. After a full-text review, 32 articles were ultimately included in the study ( 16 – 47 ). Figure 2 shows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram, illustrating the comprehensive literature screening process and results.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 32 studies included, 12 were published domestically ( 16 – 25 ), and 20 were published internationally ( 26 47 ). The most contributions came from scholars in Jiangsu Province, with a total of seven studies ( 18 , 20 , 28 , 30 , 38 , 40 , 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence to date has suggested that hyperglycaemia, hypertension, dyslipidaemia, and IR are important risk factors for DKD ( 49 , 63 ). Hyperglycemia is a widely accepted modifiable risk factor for the initiation and promotion of DKD through triggering three cardinal and inter-related pathways including overproduction of ROS, activation of apoptotic pathway and initiation of autophagy, especially in people with poor glycemic control ( 64 ). Elevated blood pressure and dyslipidemia were also identified as other major modifiable risk factors associated with the development and progression of DKD in T2DM individuals ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia is a widely accepted modifiable risk factor for the initiation and promotion of DKD through triggering three cardinal and inter-related pathways including overproduction of ROS, activation of apoptotic pathway and initiation of autophagy, especially in people with poor glycemic control ( 64 ). Elevated blood pressure and dyslipidemia were also identified as other major modifiable risk factors associated with the development and progression of DKD in T2DM individuals ( 64 ). Some studies have found that antihypertensive and lipid-lowering therapy can reduce the risk of albuminuria, kidney function decline, and progression to ESRD ( 35 , 65 ).…”
Section: Discussionmentioning
confidence: 99%